A Note on Mitosis and Meiosis in the Climbing Bamboo Melocalamus compactiflorus (Kurz) Benth. - Kumari, Lalita (Indian Forester, 1983)
Melocalamus compactiflorus flowered for the first time at Dehra Dun in December, 1980. The chromosome number of this climbing bamboo is hitherto unreported. It has now been worked out from both somatic and meiotic tissues. Young unopened leaves were used for somatic counts and young flower-buds for meiosis. Somatic chromosome measurement for Karyotypic study were made. 72 chromosomes Were counted from somatic cells and 36 bivalents in pollen mother cells. As the base number of tribe Bambuseae is recognised as X = 12, M. compactiflorus is a hexaploid.